Intra‐ and interobserver agreement for fetal cerebral measurements in 3D‐ultrasonography. Issue 8 (10th April 2018) - Albers, Maria E. W. A.; Buisman, Erato T. I. A.; Kahn, René S.; Franx, Arie; Onland‐Moret, N. Charlotte; de Heus, Roel
Abstract: The aim of this study is to evaluate intra‐ and interobserver agreement for measurement of intracranial, cerebellar, and thalamic volume with the Virtual Organ Computer‐aided AnaLysis (VOCAL) technique in three‐dimensional ultrasound images, in comparison to two‐dimensional measurements of these brain structures. Three‐dimensional ultrasound images of the brains of 80 fetuses at 20–24 weeks' gestational age were obtained from YOUth, a Dutch prospective cohort study. Two observers performed offline measurement of the occipitofrontal diameter, intracranial volume, transcerebellar diameter, cerebellar volume, and thalamic width, area, and volume, independently. VOCAL was used for calculation of the volumes. The two‐way random, single measures intraclass correlation coefficient (ICC) was used for analysis of agreement and Bland–Altman plots were configured. Intra‐ and interobserver agreement was almost perfect for occipitofrontal diameter (intra ICC 0.88, 95% CI 0.82–0.92; inter ICC 0.91, 95% CI 0.85–0.94), intracranial volume (intra ICC 0.96, 95% CI 0.91–0.98; inter ICC 0.97, 95% CI 0.96–0.98) and transcerebellar diameter (intra ICC 0.91, 95% CI 0.86–0.94; inter ICC 0.86, 95% CI 0.78–0.910). For cerebellar volume, the intraobserver agreement was almost perfect (0.85, 95% CI 0.76–0.90), whereas the interobserver agreement was substantial (0.75, 95% CI 0.44–0.88). Agreement was only moderate for thalamic measurements. Bland–Altman plots for the volume measurements are normally distributed with acceptable mean differences and 95% limits of agreement. The intra‐ and interobserver agreement of the measurement of intracranial and cerebellar volume with VOCAL was almost perfect. These measurements are therefore reliable, and can be used to investigate fetal brain development. Thalamic measurements are not reliable enough.